Gestational hypertension and risk of atopic diseases in offspring, a national-wide cohort study - Yang, Chun-Ti; Lin, Ching-Heng; Lin, Ming-Chih (Frontiers in Pediatrics, 2023)
Introduction: Gestational hypertension can lead to complications, such as preeclampsia.Preeclampsia is one of leading causes of perinatal morbidity and mortality. Abnormal placentation, immune dysregulation, and maternal inflammatory response are possible etiologies. The burden of atopic diseases is increasing worldwide. Prenatal exposure might play a role in the pathogenesis of these two diseases. The aim of this study was to evaluate the association between gestational hypertension and atopic diseases from a nationwide perspective.The primary data were retrieved from Taiwan's National Health Insurance Research Database. The Maternal and Child Health Database was used to generate links between mothers and children. From 2004 to 2019, mothers with a diagnosis of gestational hypertension were identified as cases. The control groups were matched to the cases by maternal age, neonatal gender, date of birth, at a control-to-case ratio of 4:1. Each child was reviewed to confirm the diagnosis of atopic disease. Covariates including both maternal and neonatal factors were also collected.Results: A total of 1,935,874 primiparas were enrolled in this study. After excluding 16,851 mothers with a history of hypertension, a total of 1,919,023 offspring were included in the study for the period 2004 to 2019. Gestational hypertension was associated with asthma (HR, 1.12, 95% CI, 1.02-1.23) and atopic dermatitis (HR, 1.10, 95% CI, 1.00-1.21) in offspring after controlling for cofactors.Nevertheless, gestational hypertension did not play an independent factor for allergic rhinitis (HR, 1.02, 95% CI, 0.95-1.10) or urticaria (HR, 1.02, 95% CI, 0.91-1.15).Maternal gestational hypertension increases the cumulative risk for asthma and atopic dermatitis in offspring.